The answer to your question is -32.9
Answer:
x³ + 7x² - 6x - 72
Step-by-step explanation:
Given
(x + 6)(x + 4)(x - 3) ← expand the second and third factor, that is
(x + 4)(x - 3)
Each term in the second factor is multiplied by each term in the first factor, that is
x(x - 3) + 4(x - 3) ← distribute both parenthesis
= x² - 3x + 4x - 12 ← collect like terms
= x² + x - 12
Now multiply this by (x + 6) in the same way
(x + 6)(x² + x - 12)
= x(x² + x - 12) + 6(x² + x - 12) ← distribute both parenthesis
= x³ + x² - 12x + 6x² + 6x - 72 ← collect like terms
= x³ + 7x² - 6x - 72
Answer:
perimeter = 40 feet
Step-by-step explanation:
side^2 = 100
side = 10
perimeter = 10 x 4 =40
Answer:
18
Step-by-step explanation:
multiply 7 and 3
reduce 15/5 to 3
subtract 21-3
18